A Narrative Inquiry into Communication Professionals’ Competencies in Nepal’s Development Workplaces (The Harvest, 2023)
Communication professionals in development organizations are regarded as the voice of the organization they represent. As such, it’s important that these professionals be competent at what they do. Currently, the discourse on the competencies of Nepal-based development organizations is rich and vibrant as many research endeavors and reports cover their successes and achievements every year. However, there’s little to no literature for communication professionals who ‘voice’ the very same development organizations. This narrative inquiry sheds light on how communication professionals self-assess their competencies. The outcome of this study’s exploration led to a common narrative shared by the research participants. The narrative showed Nepal’s development organization’s communication professionals holding themselves to a very high competency standard and striving to meet and exceed those standards in each responsibility they fulfilled for their organizations. This strongly implies further research is vitally necessary on Nepali communication professionals.